'Cultural Memory and Resistance in Assia Djebar's Vaste est la prison'. (2nd October 2019) - Cheref, Abdelkader
ABSTRACT: This article examines the concept of cultural memory and Resistance in Vaste est la prison by the Francophone and postcolonial Maghrebi author Assia Djebar. It also attempts to highlight the link(s) between memory and literature; and how literature engages in individual and collective memory when considering that resistance is determined by the practices of remembering and of writing. The article draws attention to the processes by which Djebar challenges and reconstructs cultural memory as a form of communal meaning in modern Algeria. Djebar embraces the Gramscian model which brings together 'theoretical ingenuity and local knowledge' while highlighting culture in the nationalist struggle for emancipation. Engaging with the works of revolutionary theoreticians such as Amilcar Cabral and Frantz Fanon, who both recognize the significance of the past in colonial and anti-colonial processes, Djebar revisits official/traditional history in the novel. She also uses a postcolonial approach that successfully de-centres the official version of history and makes space for the contribution of 'the freed and silenced'. In underlining the dialectical relationship between the novel and history, Djebar not only acknowledges Pierre Nora's pioneering work in linking memory to tangible concrete sites, identified as lieux de mémoire, but she also takes this a step further. She brings in, first, the vital importance of language (Tamazight) as the incarnation of the community's collective memory, and, second, the interconnectedness of identity, cultural memory, colonial legacies, and postcolonial studies.